A Comparative Analysis of Risk and Return Stocks: Sharia and Conventional Banking - Maharany, Indah Dewi (ITB AAS INDONESIA Surakarta, 2024)
The development of the capital market in Indonesia grows rapidly in the last few years. One of the sectors that investors are interested in is banking, both sharia and conventional. Investors must pay attention to two things, namely risk and return. This research aims to collect empirical evidence regarding the differences in return and risk of BRIS and BTPN stocks listed on Indonesia Stock Exchange (IDX), 2021 – 2023. The data analysis technique for this research uses descriptive statistical analysis, analytical prerequisite tests and hypothesis test. The results of expected return on BRIS stock was 7.96%, while the expected return on BTPN stock was 2.84%. The risk level for BRIS stock over a period of 36 months was 6.33%, while the risk level for BTPN was 3.0%. Based on research, the results show that there is a significant difference between the return and risk of BRIS and BTPN stocks during the 36 month period from January 2021 to December 2023.